STRATEGI GURU SELAMA PEMBELAJARAN DARING DALAM MENINGKATKAN KETERAMPILAN BERBICARA ANAK USIA 4-5 TAHUN DI TK GLOBAL MAJU KHATULISTIWA PONTIANAK - Kawita Kawita; Andini Andini; Aswandi Aswandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstrakThis study aims to describe the teacher's strategy during online learning in improving the speaking skills of children aged 4-5 years at Global Maju Khatulistiwa Kindergarten, Pontianak. The method used is a case study method with a qualitative research form. The subjects in the study were class teachers of group A1 at Global Maju Khatulistiwa Kindergarten, Pontianak. Data collection techniques used in this study were in-depth interviews and documentation. The results showed that: 1. The initial activities during online learning in improving the speaking skills of children aged 4-5 years were praying, greeting, singing and rhyming. 2. The core activity during online learning in improving the speaking skills of children aged 4-5 years, namely the teacher invites children to mention, imitate sounds, sing. 3. Closing activities during online learning in improving the speaking skills of children aged 4-5 years, namely the teacher asks again today's activities, informs tomorrow's activities, sings and prays before going home. Thus, the teacher's strategy during online learning in improving children's speaking skills after 4- 5 years at Global Maju Khatulistiwa Kindergarten, Pontianak has been implemented well.Keywords: Eacher Strategies During Online Learning, Speaking Skills, 4-5 Years Old Children